external trade and markets in the principality of ibn el kadi during the Ottoman era - boumoula, nabil (Journal of Social Sciences and Humanities, 2024)
Trade and market-making are among the important economic activities that have played a role in the development of peoples during the modern period, and the region of Kabyli acontributed to the greatactivitythat Algeria experiencedduring the Ottoman era, thanks to its central geographical location, whichconnects the EasternBaylek to the House of the Sultan, and also links severalancienttrade routes such as Burj Hamza, Majana, Beni Abbas Castle, Al-Biban.... This location has made it a transit area for tradecaravansbetween the east and the centre, and its supervision of the coastalstrip has opened up the possibility of opening up to the outside world through the region'sseaportssuch as Dalles, Azfoun and Bejaia. Thesefactors have helped andcontributed to internal and external commercial activity ..